MENINGKATKAN KEMAMPUAN MEMBACA DAN MENULIS SISWA KELAS I DENGAN MENGGUNAKAN MEDIA FLASH CARD SD NEGERI 006 SUNGAI BULUH KECAMTAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Indot Indot (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is motivated by the results of learning to read and write students' Indonesian language subjectsthat are still low. The purpose of this study was to improve the results of learning to read and write class I.BPrimary School 006 Sungai Buluh Singingi Hilir, Kuantan Singingi District. From the analysis of research datait was found that, the activity of teachers in the first cycle of the percentage was 70% with good categories. Afterthe second cycle, teacher activity increased to 92.5% in the very good category. Student activities, in the firstcycle get a percentage of 62.5% with enough categories, whereas in cycle II it increased to 90% in the very goodcategory. The results of the assessment of students' reading skills on the baseline score, students who completeas many as 9 students with a percentage of completeness 42.85%. cycle I, which completes as many as 13students or 61.90%. Cycle II, students who complete are 18 students or 85.71%. While the results of theassessment of students' writing skills on the baseline score, students who complete are 10 students with apercentage of 47.61%. Cycle I is 14 students or 66.66%. Cycle II, amounting to 19 students or 90.47%. From thedata from the assessment of students' reading and writing skills, it can be concluded that by using flashcardmedia can improve the results of reading and writing skills of class I.B Primary School 006 Sungai BuluhSingingi Hilir, Kuantan Singingi District.